2013
DOI: 10.4308/hjb.20.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Yeasts and Lactic Acid Bacteria (LAB) During Tempeh Production

Abstract: Yeasts and lactic acid bacteria (LAB) are commonly found in tempeh and has been studied separately. However, comprehensive study on population dynamics of yeasts and LAB during tempeh production, including the effect of the difference tempeh production methods has not been reported. This research was aimed in studying the effect of different methods of tempeh production applied in tempeh home industry on the dynamics of yeast and LAB communities. Population dynamics was expressed as both changes of colony numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…During the solid-state fermentation of soybean, the molds incre ase the vitamin B6, riboflavin, and nicotinic acid (Bisping et al 1993). Efriwati et al (2013) reported yeast occurrence in the fermentation of soybean tempeh and the diversity of yeast was depended on the method of tempeh fermentation. The predominant yeast in over-fermented tempeh, Kluyveromyces marxianus, showed to have the species abundance of 36.98%.…”
Section: Resultsmentioning
confidence: 99%
“…During the solid-state fermentation of soybean, the molds incre ase the vitamin B6, riboflavin, and nicotinic acid (Bisping et al 1993). Efriwati et al (2013) reported yeast occurrence in the fermentation of soybean tempeh and the diversity of yeast was depended on the method of tempeh fermentation. The predominant yeast in over-fermented tempeh, Kluyveromyces marxianus, showed to have the species abundance of 36.98%.…”
Section: Resultsmentioning
confidence: 99%
“…While S. boulardii has been shown to be effective in preventing the recurrence of Clostridium difficile-induced pseudomembranous colitis as well as the antagonistic action of E. coli, the long-term advantages of using spores as probiotics is that they are heat-stable and can survive transit across the stomach barrier, properties that cannot be assured with other probiotic bacteria that are given in the vegetative form [61]. Yeasts are commonly present in many fermented foods [6,11,12,62] and starter culture [63]. Spore-forming bacteria could also be part of the microbial consortium in traditional Indonesian fermented foods, such as tempe [5] and tape [6,64] as well as their starter cultures [62].…”
Section: Potential Of Lactic Acid Bacteria Isolated From Indonesian Fmentioning
confidence: 99%
“…In tempe fermentation, soybeans are soaked overnight prior to inoculation with starter culture containing Rhizopus oligosporus as the primary microorganism. Acid fermentation involving LAB takes place during the soaking [10,11] and some growth of lactic acid bacteria commonly occurs during the stage of mold growth [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bacteria in tempeh is also known as one of the factors that play a role in the formation of a bitter taste in tempeh (Barus et al 2008). A diverse array of lactid acid bacteria and yeasts also play important role in Indonesian tempeh production (Efriwati et al 2013).…”
mentioning
confidence: 99%